Chemical Weathering - Duarte, Isabel M.R. (2018)
Living reference work entry First Online: 22 July 2017 Definition: Weathering of rocks caused by the chemical action of water containing atmospheric oxygen, carbon dioxide, and some organic acids in solution on the rock-forming minerals leading to an adjustment of the mineralogical composition with the formation of new minerals, like hydrous phyllosilicates, iron oxides/hydroxides, soluble salts, and other alteration products, consisting in rocks decay by their chemical decomposition. Introduction: Chemical processes need water, being carried out more rapidly at higher temperature, so they are common in warm and wet climates. There are different types of chemical weathering processes , such as solution, hydration, hydrolysis, carbonation, oxidation, reduction, and chelation. Some of these reactions occur more easily when the water is slightly acidic. Weathering of rocks is a fundamental phenomenon for the formation of the soil,... This is a preview of subscription content, log in to check access Copyright information © Springer International Publishing AG 2017